The Neglected "R" in the Risk-Needs-Responsivity Model: A New Approach for Assessing Responsivity to Correctional Interventions. (26th October 2018) - Duwe, Grant; Kim, KiDeuk
Abstract: Prevailing correctional practice holds that offenders should be assigned to interventions on the basis of assessments for risk, needs, and responsivity. Assessments of responsivity, however, typically consist of little more than a checklist of items such as motivation, gender, language, or culture. We introduce a new actuarial approach for assessing responsivity, which focuses on predicting whether individuals will desist after participating in an intervention. We assess responsivity by using multiple classification methods and predictive performance metrics to analyze various approaches for prioritizing individuals for correctional interventions. The results suggest that adding an actuarial responsivity assessment to the existing risk and needs assessments would likely improve treatment assignments and further enhance the effectiveness of an effective intervention. We conclude by discussing the implications of more rigorous responsivity assessments for correctional research, policy, and practice.